Breaking the model: Does technical efficiency propel or hinder bank risk? Evidence from the Chinese banking industry - Lin, X.; Gulamhussen, M. A.; Zhai, J. (Emerging Markets Finance and Trade, 2025)
This study examines the relationship between technical efficiency and bank risk using data from Chinese commercial banks from 2007 to 2020. Employing a stochastic frontier model, we measure individual technical efficiency (ITE), group technical efficiency (GTE), and meta-efficiency (MEF) to capture both individual and group efficiency variations. Our findings indicate that higher technical efficiency generally increases bank risk, with the effect being more pronounced at the individual level. In the post-COVID period, this relationship persists at the individual level but weakens at the group levels, suggesting that regulatory interventions have mitigated systemic risks while allowing efficiency-driven risk-taking to continue. Further analysis reveals that higher government ownership amplifies the risk-enhancing effect of efficiency, while business growth helps mitigate risk exposure. Robustness and endogeneity tests confirm the validity of our results. These findings contribute to the ongoing discussion on bank efficiency, risk management, and regulatory oversight, offering insights into how technical efficiency shapes financial stability in an evolving banking landscape.